Proptech and the private rental sector: New forms of extraction at the intersection of rental properties and platform rentierisation. - Rogers, Dallas; Maalsen, Sophia; Wolifson, Peta; Fields, Desiree (Urban Studies (Sage Publications, Ltd.), 2024)
Private renting increasingly comprises a complex ecosystem of actors who assemble housing within the market, and collect rental income and data from tenants, and data on the material assets themselves. Our analysis – at the intersection of rentier and platform capitalism – focuses on landed (material real estate) and technological (digital infrastructure and data) property in Australia's private rental system. Drawing out relationships between the various actors – landlords, rental property managers and real estate agencies, software developers and providers, property developers and investors – and both their properties and their uses of Proptech (property technology), we show how housing and technology are being leveraged for profit in new ways. In Australia, landed property retains its precedence for established (individual and institutional) landlords, whose interest in Proptech relates to enhancing or value-adding to rental housing assets. For Proptech and institutional real estate players seeking to consolidate both landed and technology property, capturing the tech landscape is increasingly important; indeed, securing control and/or consolidation of technology property is a key motivation for building and/or using Proptech among the largest property developers. Our findings show how rent extraction operates across and between different types and scales of property and market actors, and in new ways that differentiate the figure of the rentier while upholding the dynamics of the rentier model.